Le commerce compensé et la Banque nationale du Canada - Courville, Léon (Assurances, 1986)
Trade by barter has gained considerable importance in international trade. It especially avoids movements of funds which, if significant, can have a devastating effect on both supplier and buyer, particularly when a Third World Country is the buyer. The supplier wants to sell, but the buyer cannot pay cash, even on a long-term basis. Barter, which the author also refers to as counter trade, offers an interesting solution to the problem, as discussed in this article by Mr. Léon Courville, Senior Vice President, Economic and International Affairs at the National Bank of Canada.